The Effect of financial literacy and education level on the profitability of micro and small enterprises in Indonesia - Hanifil fiqri; Ramel Yanuarta RE (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of financial literacy as measured by ownership of savings accounts and knowledge of the official financial institutions providing loans, and the level of education on the profits of Micro and Small Enterprises in Indonesia. By considering the characteristics of heterogeneous data and outliers, this study uses a quantile regression method with a confidence level (∝ = 0.05). The data used is secondary data from IFLS (Indonesia Family Life Survey) waves 4 and 5. 8,118 MSEs meet the criteria as samples. The analysis results show that the savings ownership of MSE owners has a significant positive effect on the MSE profit quantile on all business scales compared to MSE owners who do not have a savings account. Still, the effect is lower in the large quantile group. Furthermore, knowledge of lenders' official financial institutions has a significant positive impact on MSE profit quantiles across all business scales compared to MSE owners who do not know lenders’ official financial institutions; the effect is lower in the larger MSE income quintile group. Meanwhile, the education level of MSE actors has a significant positive impact, but only on the medium to high-scale MSE; the effect is higher for the large MSE profit quintile group.